Numerical modeling and economic evaluation of two multi-effect vacuum membrane distillation (ME-VMD) processes - Zhang, Y.; Peng, Y.; Ji, S.; Qi, J.; Wang, Shaobin (Elsevier BV, 2017)
© 2017 Elsevier B.V. A hollow fiber membrane module cascaded with a heat exchanger to recover the latent heat of vapor is a one-stage vacuum membrane distillation (VMD) unit. In this work, two multi-effect VMD (ME-VMD) systems, first-stage heating and inter-stage heating processes with n one-stage-VMD units cascaded together, were firstly considered and compared in terms of efficiency using computational fluid dynamics (CFD). The inter-stage heating ME-VMD system had a relatively high water recovery, however, its gained output ratio (GOR) was low and the system complexity and operating cost increased due to the presence of the heaters in each stage. Thus, we focused on the first-stage heating ME-VMD system. An ME-VMD system containing 30 one-stage VMD units with first-stage heating was then evaluated coupling with the mathematic model of single module via CFD, and an economic evaluation model was established. The effects of feed inlet temperature and stage number on the distillate flux, water recovery and GOR were comprehensively discussed. The highest GOR could reach to 12.1. The water production cost mainly depended on the heat exhaustion and the lowest cost was estimated at $0.59/t for an optimal four-stage ME-VMD system with first-stage heating, which can be competitive to the reverse osmosis technique.